Barriers and Coping Strategies in Practicing Therapeutic Communication in English Among Second-Semester Midwifery Students - Chairuddin, Chairuddin; Fithriani, Rahmah; Siwi, Purwanto (ITScience (Information Technology and Science), 2025)
Therapeutic communication in English has become increasingly important in midwifery education, considering global health standards and the need for effective patient interaction across languages. Despite this, students often face barriers that hinder their ability to communicate therapeutically in English. This study investigates the internal and external barriers experienced by second-semester midwifery students in practicing therapeutic communication in English, and explores the coping strategies they employ. A qualitative descriptive design was applied with 26 second-semester midwifery students selected purposively. Data were collected through adapted questionnaires and semi-structured interviews. Thematic analysis was used to identify categories of barriers and coping strategies. The findings revealed that internal barriers included shyness, lack of confidence, low motivation, and fear of mistakes, with shyness being the most dominant. External barriers consisted of embarrassment, limited vocabulary, lack of preparation, grammatical errors, and peer judgment, with embarrassment identified as the most critical. Coping strategies involved preparation, relaxation, positive thinking, concentration, and peer support, with preparation and relaxation as the most effective. Practicing therapeutic communication in English presents multidimensional challenges for students, combining psychological, social, and linguistic difficulties. Integrating English for Specific Purposes (ESP) modules, simulation, flipped classrooms, and peer-based learning into midwifery curricula can enhance students’ confidence, communication skills, and readiness for international clinical practice.